Performance of GPS-TEC assisted NTCM-model to describe the East-African equatorial ionosphere. Issue 11 (1st December 2021) - Getahun, B.; Nigussie, M.
Abstract: NTCM is a relatively simple climatological ionosphere model. However, its weather ionosphere characteristic specification capability is limited. Also, its nowcasting and forecasting performance of the East-African equatorial ionosphere has not yet been tested. Therefore, this paper demonstrates techniques of changing NTCM to an ionospheric weather model that nowcasts and forecasts VTEC for East Africa. It has been done by adapting the model to quiet day VTEC from nineteen GNSS receivers in East Africa in 2013 and 2014. Then, performances of the model in nowcasting and forecasting VTEC, before and after the adaption, have been investigated compared to observed VTEC. We have found that NTCM, after adaptation, represents observed features of diurnal variations of VTEC and equatorial ionization anomaly (EIA) much better than before adaptation. After adaptation, the mean and standard deviation of daily mis-modelings are comparable with the mean and standard deviation of yearly mis-modelings. The study showed that NTCM, after adaptation to a reference station, performs better than before ingestion at the stations nearby the reference station; however, its performance decreases at the locations far away from the reference station. In addition, after ingestion, one hour ahead prediction of NTCM is found to be the best compared to longer time predictions.